2008
DOI: 10.2298/vsp0801047b
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine stress protocols for myocardial perfusion imaging

Abstract: The safety and efficacy of adenosine pharmacological stress is even better with concomitant exercise. In the light of these benefits we recommend AdenoEX whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
4
0
6
Order By: Relevance
“…This is very important finding, since a reversible defect on the myocardial perfusion imaging (MPI) by single photon-emission computed tomography (SPECT) is the only available diagnostic tool that can independently predict the risk of nonfatal MI. Therefore, stress perfusion studies should be reported documenting defect severity (mild, moderate, severe), size (small, moderate, large) and reversibility to provide essential risk stratification (2,4,5,6). The value of MPI comes from the ability to identify and quantify the degree of jeopardized myocardium during stress tests.…”
Section: Determination Culprit Lesion the Current Definition Of Culprmentioning
confidence: 99%
See 1 more Smart Citation
“…This is very important finding, since a reversible defect on the myocardial perfusion imaging (MPI) by single photon-emission computed tomography (SPECT) is the only available diagnostic tool that can independently predict the risk of nonfatal MI. Therefore, stress perfusion studies should be reported documenting defect severity (mild, moderate, severe), size (small, moderate, large) and reversibility to provide essential risk stratification (2,4,5,6). The value of MPI comes from the ability to identify and quantify the degree of jeopardized myocardium during stress tests.…”
Section: Determination Culprit Lesion the Current Definition Of Culprmentioning
confidence: 99%
“…Pharmacologic stress can be done with vasodilator agents (adenosine, dipyridamole, adenosine triphosphate, or selective adenosine A2a receptor agonist) or with inotropic and chronotropic agents (dobutamine or arbutamine). Patients with left bundle branch block (LBBB) or electronically paced rhythms may have anteroseptal perfusion defects with exercise or dobutamine perfusion imaging unrelated to stenosis of the left anterior descending artery and hence vasodilator stress testing is recommended in these patients (6,7,8,9). Adenosine and dipyridamole stress have been used in combination with exercise especially in patients with limited exercise capacity.…”
Section: Coronary Artery Disease -Exercise and Pharmacologic Stress Testmentioning
confidence: 99%
“…Abbreviated adenosine (3 to 4 minutes) protocols are also available. [ 12 ] Similarly, IV dipyridamole is infused over the same time period at a dose of 0.6 mg/kg per minute. A dose of 3 to 5 mg/kg of aminophylline given intravenously is the antidote for adverse effects due to dipyridamole.…”
Section: Dosagesmentioning
confidence: 99%
“…Sadašnja praksa uključuje upotrebu vazodilatatora (adenozin, dipiridamol) i inotropnog agensa (dobutamin) kod bolesnika koji nisu u mogućnosti da adekvatno budu podvrgnuti fizičkom testu opterećenja. U dijagnostici koronarne arterijske bolesti (KAB) farmakološki testovi opterećenja, uz PSM danas se upotrebljavaju kod oko 40% slučajeva [1][2][3][4][5] . Testovi fizičkog opterećenja rade se kod bolesnika koji mogu adekvatno postići maksimum fizičkog opterećenja.…”
Section: Uvodunclassified